2012
DOI: 10.1002/ceat.201100305
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation of a Pilot Scale Vacuum Gas Oil Hydrocracking Unit by the Space‐Time CE/SE Method

Abstract: This work introduces a modified space-time conservation element/solution element (CE/SE) method for the simulation of the dynamic behavior of a pilot-scale hydrocracking reactor. With this approach, a four-lump dynamic model including vacuum gas oil (VGO), middle distillate, naphtha and gas is solved. The proposed method is capable of handling the stiffness of the partial differential equations resulting from the hydrocracking reactions. To have a better judgment, the model is also solved by the finite differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Recently, the application of CE/SE method had been extended to simulation of explosive [23,24], aeroacoustics [25], crystallization [26], heat conduction [27], relativistic hydrodynamics [28,29], chemical reaction [30,31], et al Lim et al [18,19] utilized the CE/SE method to solve SMB model equations and found the accuracy and computational efficiency to be simultaneously improved.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the application of CE/SE method had been extended to simulation of explosive [23,24], aeroacoustics [25], crystallization [26], heat conduction [27], relativistic hydrodynamics [28,29], chemical reaction [30,31], et al Lim et al [18,19] utilized the CE/SE method to solve SMB model equations and found the accuracy and computational efficiency to be simultaneously improved.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the space-time domain is discretized two times by: a rhomboid mesh and a rectangular mesh. The theoretical framework of the CE-SE method for the nonfractional case is well established and it has been applied to a large number of real problems with successful results [26][27][28][29][30][31][32][33]. An important property of the fractional differential operators is the nonlocality which is achieved with the discretization of the integral associated with the fractional derivative.…”
Section: Introductionmentioning
confidence: 99%